Life cycle assessment of perovskite solar cell based on rapid convective deposition at electron transport layer - Detnatthawut, Dissapat; Varabuntoonvit, Viganda; Lohawet, Khathawut; Laewprajak, Anusit; Kumnorkaew, Pisist (Asia-Pacific Journal of Science and Technology, 2022)
Photovoltaic (PV) devices made of perovskite materials have much potential to become an excellent source of energy with high-power conversion efficiency (PCE) as well as being environment-friendly. Perovskite solar cells (PSCs) will be a rising star in the PV market share due to their efficiency that has increased substantially over the past few years. PSCs have additional advantages of being environment-friendly, having high PCE, and are low cost. This paper reports on a life cycle assessment (LCA) of PSCs with an electron transport layer produced by a rapid convective deposition method instead of the conventional spin coating technique used in other reports. The advantage of using the rapid convective deposition technique is that it offers low material consumption compared to the conventional spin coating technique. LCA can assess the environmental consequences and energy consumption of a product over its whole life cycle according to ISO 14040:2006 and ISO 14044:2006. In the LCA process, the greenhouse gas (GHG) emissions and the energy payback time (EPBT) of PSCs were compared to those of crystalline silicon (c-Si) solar cells, both mono-Si solar cells and multi-Si solar cells. The LCA results showed that PSCs had the shortest EPBT compared to other solar PV technologies. Future research developments should improve the PCE, increase the lifetime, and reduce the materials and energy consumption of PSCs to further reduce GHG emissions and EPBT.